2019
DOI: 10.1016/j.enpol.2019.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Fuel poverty and Well-Being:A consumer theory and stochastic frontier approach

Abstract: Evidence and conventional wisdom suggest that general poverty has a negative effect on the well-being of individuals. However, the mechanisms through which this effect occurs are not well-understood. In this paper we analyse the effect of general and fuel poverty as well as the social dimension through peer comparison on the objective and perceived well-being of households. We develop a novel approach to analyse fuel poverty and well-being based on consumer theory. Individual preferences are modelled using ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 37 publications
(22 reference statements)
1
28
1
Order By: Relevance
“…Results from our study revealed that an increase in energy deprivation heightened one's chances of being mentally unhealthy. Unlike previous studies [18][19][20][21], we found channels or indicators such as the lack of a refrigerator, electricity and modern cooking fuel inaccessibility, mobile phone deprivation and indoor air pollution to significantly deteriorate the mental health of household heads. We concluded by urging policymakers to adopt a holistic approach in solving issues of energy poverty where simultaneous attention is given to all the dimensions of energy poverty since they collectively have detrimental effects on mental health, especially in a developing country setting.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Results from our study revealed that an increase in energy deprivation heightened one's chances of being mentally unhealthy. Unlike previous studies [18][19][20][21], we found channels or indicators such as the lack of a refrigerator, electricity and modern cooking fuel inaccessibility, mobile phone deprivation and indoor air pollution to significantly deteriorate the mental health of household heads. We concluded by urging policymakers to adopt a holistic approach in solving issues of energy poverty where simultaneous attention is given to all the dimensions of energy poverty since they collectively have detrimental effects on mental health, especially in a developing country setting.…”
Section: Introductioncontrasting
confidence: 99%
“…Yet, despite this growing interest in mental health and energy poverty, relatively little is known about how energy deprivation influences mental wellbeing [18] in developing economies, particularly in SSA, as most of these studies [18][19][20][21] have been concentrated in advanced economies. For example, using energy efficiency investments in homes of low-income areas to represent energy poverty, Gray et al [48] examined the linkages between energy poverty and the mental health of residents in a quasi-experimental field survey in Wales.…”
Section: Energy Poverty and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Current work on energy poverty is more focused on traditional, objective, and infrastructure-related variables than on self-perceived energy poverty as determinants and implications. Our research brings an unconventional perspective to some neglected facets of the impact subjective energy poverty has upon life satisfaction, in more precise terms than the negative relationship already unveiled in previous studies [26,[98][99][100]. Strengthening and expanding this literature niche may be a crucial aspect in increasing the awareness about the major role played by energy policies for the wellbeing of a society, in connection to health and social measures.…”
Section: Discussion Conclusion and Research Limitationsmentioning
confidence: 85%